Degradasi Hutan Bakau Akibat Pengambilan Kayu Bakar oleh Indutri Kecil Gula Kelapa di Cilacap - Tumisem, T; Suwarno, S (Forum Geografi, 2008)
A study on degradations mangrove forest due to firewood exploitation by coconut palm sugar home industry in Cilacap. Information on social economic aspect and respons of coconut palm sugar home industry to using fuel substitutions were collected by using a questioner. The potential of mangrove as a firewood source was estimated by quadrat method. The study has been carried out on dry and rainy season. The wood production of available 8000 ha of mangrove from Cilacap primarily Rhizophora apiculata Linn and Rhizophora mucronata Lamk were 3.249.920 m³. The results showed that the declining of mangrove was about 19,250 m² in dry season and 26,551 m² in rainy season, this was correlated with the amount of nira to be processed that was 0,782 m³ in dry season and 1,079 m³ in rainy season. Deforestation of mangrove forest due to change of mangrove zonation. Rhizophora apiculata Linn and Rhizophora mucronata Lamk will be domination Nypa fruticans that is shown superficiality to continent form.